2011
DOI: 10.1155/2011/827565
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3Expression in Liver Correlates with the Degree but Not the Cause of Inflammation

Abstract: Patients with chronic viral hepatitis display increased expression of Foxp3 in liver, suggesting that Tregs expansion contributes to persistent infection. The purpose of this study was to elucidate whether the expression of Foxp3 relates not to the viral infection but to the resulting liver inflammation. Liver biopsies obtained from 69 individuals (26 chronic HBV hepatitis, 14 chronic HCV hepatitis, 11 nonalcoholic fatty liver disease, 8 autoimmune diseases, 2 methotrexate-related toxicity, and 8 controls) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 51 publications
3
39
0
6
Order By: Relevance
“…This observation is also in accordance with previous reports [24,[50][51][52]. Moreover, although CD8 + /Foxp3 + cells have been described in CHC biopsies [31,53],they were under-represented in our studied series, as in other reports [51,52].…”
Section: Mann-whitney U-test and Unpaired T-testsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is also in accordance with previous reports [24,[50][51][52]. Moreover, although CD8 + /Foxp3 + cells have been described in CHC biopsies [31,53],they were under-represented in our studied series, as in other reports [51,52].…”
Section: Mann-whitney U-test and Unpaired T-testsupporting
confidence: 94%
“…Accumulating evidence indicates that patients with chronic viral hepatitis display an increased number of Treg cells in peripheral blood or liver; however, the increment of Treg cells in CHC and their role in liver damage development is still a matter of debate [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…T regs secrete anti-inflammatory signals, inhibit macrophage migration, and induce noninflammatory M2-like macrophage differentiation (35). In addition, defects in T reg function are considered to play a role not only in autoimmune diseases, such as autoimmune hepatitis (36), but also in other causes of hepatic inflammation (37,38). In agreement with an anti-inflammatory property of lyso-PCs, we detected strong negative relationships of total lyso-PCs and lyso-PC C16:0 with hs-CRP levels in our subjects with NAFL.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, peripheral and intrahepatic Treg frequency correlated with disease activity. This is further supported by a report which showed that Treg frequency is generally elevated in inflamed livers irrespective of its cause [32]. If there is not a global defect of Treg numbers in AIH, the question rises why the attracted Treg are not able to suppress hepatic inflammation?…”
Section: Regulatory T Cells In Aihmentioning
confidence: 65%